Genetic and antigenic characterization of enterovirus 71 in Ho Chi Minh City, Vietnam, 2011. - Le Phan Kim Thoa; Pai-Shan Chiang; Truong Huu Khanh; Shu-Ting Luo; Tran Ngoc Hanh Dan; Ya-Fang Wang; Tang Chi Thuong; Wan-Yu Chung; Nguyen Thanh Hung; Jen-Ren Wang; Le Nguyen Thanh Nhan; Le Quoc Thinh; et al. (PLoS ONE, 2013)
Enterovirus 71 (EV71) frequently causes fatal infections in young children in Asia. In 2011, EV71 epidemics occurred in southern Vietnam. We conducted genetic and antigenic analysis of the EV71 isolates and found that 94% of them were genotype C4a related to two lineages circulating in China and 6% were genotype C5 which have circulated in Vietnam since 2003. Antigenic variants were not detected. EV71 vaccines are being developed. Longitudinal enterovirus surveillance data are critical to formulate vaccination policy in Vietnam.